2020
DOI: 10.3390/nano10081604
|View full text |Cite
|
Sign up to set email alerts
|

Removal of As(III) from Water Using the Adsorptive and Photocatalytic Properties of Humic Acid-Coated Magnetite Nanoparticles

Abstract: The oxidation of highly toxic arsenite (As(III)) was studied using humic acid-coated magnetite nanoparticles (HA-MNP) as a photosensitizer. Detailed characterization of the HA-MNP was carried out before and after the photoinduced treatment of As(III) species. Upon irradiation of HA-MNP with 350 nm light, a portion of the As(III) species was oxidized to arsenate (As(V)) and was nearly quantitatively removed from the aqueous solution. The separation of As(III) from the aqueous solution is primarily driven by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
4
0
3
Order By: Relevance
“…•− produced from the conduction band (CB) of Pt−TiO 2 was responsible for As(III) oxidation at pH 3.0 under visible light. Pham et al 12 suggested that 1 O 2 was also responsible for the oxidation of As(III) by the humic acid-modified magnetite nanoparticles at pH 6.0 under UV irradiation. Apart from aqueous ROS, the oxidizing species formed on the surface of photocatalysts also contribute to As(III) oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…•− produced from the conduction band (CB) of Pt−TiO 2 was responsible for As(III) oxidation at pH 3.0 under visible light. Pham et al 12 suggested that 1 O 2 was also responsible for the oxidation of As(III) by the humic acid-modified magnetite nanoparticles at pH 6.0 under UV irradiation. Apart from aqueous ROS, the oxidizing species formed on the surface of photocatalysts also contribute to As(III) oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Photocatalysis is a technique that, on many occasions, needs to be combined with other physical processes to improve the pollutant removal efficiency. In this sense, P. Pham et al [ 12 ] synthesized materials with adsorptive and photochemical properties. These materials are based on magnetite (MNP) covered by humic acid substances (HA).…”
mentioning
confidence: 99%
“…La toxicidad de las especies de arsénico depende del estado de valencia, la especiación, la disponibilidad y las especies animales o tipos de células expuestas. La especie de arsénico trivalente es considerablemente más tóxica que la especie pentavalente, debido a su mayor capacidad de ligarse a tioles de biomoléculas, como ácido lipoico, residuos de cisteína de enzimas o proteínas 133 . La biodisponibilidad del As está determinada principalmente por la especiación, por lo tanto, la oxidación de As (III) a As (V) es necesaria para la remediación eficaz del arsénico 28 .…”
Section: Arsénico Como Contaminante Y Especiación En Solución Acuosaunclassified
“…En un trabajo reciente Pham et al 133 estudiaron la capacidad de nanopartículas de magnetita recubiertas de ácidos húmicos para actuar como materiales adsorbentes y fotocatalizadores de la oxidación de As (III). Estos autores realizaron ensayos de fotocatálisis en presencia de sorbato de potasio, un desactivador de estados triplete mediante procesos de transferencia de energía.…”
Section: Arsénico Totalunclassified
See 1 more Smart Citation